Constraining Low‐Altitude Lunar Dust Using the LADEE‐UVS Data. Issue 11 (18th November 2021) - Sharma, H.; Hedman, M. M.; Wooden, D. H.; Colaprete, A.; Cook, A. M.
Abstract: Studying lunar dust is vital to the exploration of the Moon and other airless planetary bodies. The Ultraviolet and Visible Spectrometer on board the Lunar Atmosphere and Dust Environment Explorer spacecraft conducted a series of Almost Limb activities to look for dust near the dawn terminator region. During these activities the instrument stared at a fixed point in the zodiacal background off the Moon's limb while the spacecraft moved in retrograde orbit from the sunlit to the unlit side of the Moon. The spectra obtained from these activities probe altitudes within a few kilometers of the Moon's surface, a region whose dust populations were not well constrained by previous remote‐sensing observations from orbiting spacecraft. Filtering these spectra to remove a varying instrumental signal enables constraints to be placed on potential signals from a dust atmosphere. These filtered spectra are compared with those predicted for dust atmospheres with various exponential scale heights and particle size distributions to yield upper limits on the dust number density for these potential populations. For a differential size distribution proportional to s −3 (where s is the particle size) and a scale height of 1 km, we obtain an upper limit on the number density of dust particles at the Moon's surface of 142 m −3 . Plain Language Summary: The Moon has a tenuous atmosphere of dust particles. It is important to study this dust environment in order to develop solutions for dust‐related problems with exploration of the lunar surface, as well as understand the effects of dust transport on other airless planetary bodies. Lunar Atmosphere and Dust Environment Explorer's Ultraviolet and Visible Spectrometer made a series of Almost Limb observations that enable us to probe the Moon's dust atmosphere at altitudes ranging from 1 and 10 km above the surface. Data from these observations are processed and compared to the predicted signals from a variety of different dust populations. These comparisons yield new upper limits on dust density within a few kilometers of the lunar surface, providing additional constraints on dust population at low altitudes. Key Points: Lunar Atmosphere and Dust Environment Explorer's Ultraviolet And Visible Spectrometer made a series of observations that enable us to probe the Moon's dust atmosphere at altitudes between 1 and 10 km These observations are filtered to isolate dust signals and are compared to predicted dust atmospheres For a dust population with power law size distribution of index −3 and scale height 1 km, the upper limit on the dust density is 142 m −3